Analisis Tingkat Persaingan Industri Perbankan Syariah Periode 2016-2020 - Indrayana Girindra Putra; Nugroho Sumarjiyanto Benedictus Maria (Universitas Diponegoro, 2024)
This study aims to analyze the impact of the merger of three dominant-asset Islamic banks on the level of competition in the Islamic banking sector, observed from pre-merger and post-merger conditions, as well as its determining factors. The research uses panel data from 14 banks for the pre-merger condition (2016-2020) and 11 banks for the post-merger condition (2021-2022), applying the Panzar-Rosse Model (H-Stat). The results indicate that the Islamic banking industry in Indonesia exhibits monopolistic market structures in both pre-merger and post-merger conditions. The impact of the merger led to a decrease in the competition level within the industry, as shown by the H-Stat result of 0.949 for the pre-merger condition and 0.910 for the post-merger condition. This study demonstrates that when companies with dominant assets in an industry merge, it results in reduced competition, as the newly formed entity possesses excessive capabilities while other companies are unable to compete effectively.